Physiological bases of ventricular defibrillation - Amanda Claudia Barco Lima; Belkys Caridad Pedroso Araujo; Diana Laura García Pérez; Víctor René Navarro Machado; Milagros León Regal (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Ventricular defribrillation is a basic procedure from an adequate cardio-pulmonary-cerebral resuscitation, but its principles are not commonly approached in literature. This work was aimed at describing the physiological basis of ventricular defibrillation for which it was, in the first quarter of 2018, a documentary review which included 21 bibliographical references. It was concluded that these bases integrate the cellular functions of the heart, the physical-molecular cellular modifications which condition arrythmia or are produced due to hypoxia, the changes on the cardiac tissue which allow the passage of electrical cardiac activity and the characteristics of the electrical shock wave of the defibrillator. Defibrillation stops cardiac electrical activity and allows the action potential start of its pacemaker cells.. The efficacy of the procedure depends on the metabolic condition of the myocardium (due to the cause and the time cardiac failure) and the correct performance of the defibrillation protocol.